Food and fluid intakes in female adolescent judo athletes before competition - Boisseau, N.; Vera-Perez, S.; Poortmans, J. R. (Pediatric Exercise Science, 2005)
Judo is a weight-class sport, meaning that there are weight-defined classes in competitions. Regular body weight restrictions and/or nutritional imbalances can alter growth and maturation states in adolescents. The aim of the present study was to estimate to what extent female judo athletes (age 16.1 ± 0.3 years) modified food and drink intakes 3 weeks and 1 week before competition. Our findings indicate that unbalanced dietary intakes and 'weight cutting' might occur in female adolescent competitors. We conclude that dietary recommendations are compulsory in order to educate coaches and young judokas about adequate nutrition and safe weight control behaviors, as well as the dangers of rapid weight loss and dehydration during adolescence.